Dominance of goethite over hematite in iron oxides of mineral dust from Western Africa: Quantitative partitioning by X‐ray absorption spectroscopy. Issue 22 (21st November 2014) - Formenti, P.; Caquineau, S.; Chevaillier, S.; Klaver, A.; Desboeufs, K.; Rajot, J. L.; Belin, S.; Briois, V.
Abstract: This paper reports on the X‐ray absorption analysis of samples of mineral dust emitted from or transported to Western Africa. We found that iron oxides account, by mass, for 38% to 72% of the total elemental iron. They are composed of minerals in the Fe(III) oxidation state: goethite (FeO· OH) and hematite (Fe2 O3 ). The apparent fraction of iron oxide attributed to goethite is higher than hematite regardless of the source region from which the dust originated. The goethite percent content of iron oxides is in the range 52–78% (by mass), the highest values being measured for dust originating in the Sahel. The limited number of samples analyzed and the sample‐to‐sample variability prevent us from concluding firmly on the regional variability of the goethite‐to‐hematite ratio. Based on the experimental data on mineralogical composition and on concurrent measurements of the number size distribution, the optical properties of mineral dust have been calculated in a Mie approximation for homogeneous spherical particles. At 550 nm, the single‐scattering albedo ω 0 ranges between 0.89 and 0.93, the asymmetry factor g ranges between 0.76 and 0.8 and the mass extinction efficiency k ext varies between 0.5 and 1.1 m 2  g −1 ; these values are all in the range of those from independent direct measurements. Neglecting the partitioning between hematite and goethite and the assimilation of iron oxides by hematite, as it is often done with models, lowers the single‐scattering albedo and increases the asymmetry factor in the UV‐visible spectral region below 550 nm. The mass extinction efficiency is insensitive to the nature of the iron oxides but rather responds to variations in the number size distribution. The mineralogy of iron oxides should therefore be taken into account when assessing the effect of mineral dust on climate and atmospheric chemistry, in particular via interactions involving photolysis. Key Points: Goethite exceeds hematite in African mineral dust Calculation of optical properties in dust models have to be revised